The effect of chocolate consumption (Theobroma cacao L.) on level of blood cholesterol and triglyceride in hypertension patients at Jatiroto Health Center, Indonesia - Muzaroah Ermawati Ulkhasanah; Suharyo Hadisaputro; Rr. Sri Endang Pujiastuti (GHMJ (Global Health Management Journal), 2019)
Background: Hypertension is influenced by lifestyle factors such as high fat intake which has the potential for high blood cholesterol level. Cocoa products, which are rich sources of flavonoids, have been shown to reduce blood pressure and the risk of cardiovascular disease.Aims: The purpose of this research is to examine the dark chocolate consumption in decreasing the level of blood cholesterol and triglyceride in hypertension patients.Methods: This research is a quasi-experiment study with pre and post and control group design. There were thirty two (32) hypertensive patients selected from Jatiroto Health Center in June-July 2018 using a random sampling technique. The respondents were then divided to (1) a control group where patients were prescribed to a popular non-pharmacological therapy Simvastatin and (2) an intervention group where the respondents were prescribed with Simvastatin and also received an additional dark chocolate 60gr/day (given twice a day, each 30gr) for 15 days. A spectrophotometer glycerol phosphate oxidase (GPO-POD) with 546 nm wavelength was employed to measure the levels of blood cholesterol and triglyceride. The significant mean difference between pre and posttest, and the changes between control and intervention group were defined by statistical analysis T-test.Results: This study acknowledged that the prescribed simvastatin alone presents a significant contribution to decrease the cholesterol level at 14.40 point (p value = 0.041), however, the generic is not enough to deliver a significant effect to the decrease of triglyceride level in the hypertension patients (p value = 0.361). A great contribution to the depression of cholesterol and triglyceride level in the hypertensive respondent was observed if simvastatin prescription was combined with a provision of 60 gram dark chocolate, respectively to the level of 57.06 and 38.41 mg/dL with p value = 0.001. The addition of dark chocolate in the simvastatin prescription will significantly reduce the blood cholesterol level (p value = 0.020), but not really effective to reduce the triglyceride (p value = 0.560).Conclusion: The findings suggest that giving dark chocolate to the hypertensive patients who receive simvastatin prescription will decrease the cholesterol and triglyceride levels greater than the consumption of simvastatin drugs alone. Keywords: Dark chocolate, Simvastatin, Hypertension, Cholesterol, Triglyceride Received: 25 August 2018, Reviewed: 04 September 2018, Received: in revised form 23 February 2019, Accepted: 26 February 2019 DOI: 10.35898/ghmj-31552